The Existence of Customary Land and its Utilization Pattern for Tourism Business - I Made Suwitra; I Ketut Sudiarta; I Ngurah Suryawan; Dimas Imaniar; Niko Pahlevi Hentika (RIRAI Publisher, 2023)
The purpose of this study are: (1) A comparison of the existence of customary land rights owned by indigenous villages in Gianyar Regency and those owned by indigenous communities in Banyuwangi Regency.; and (2) patterns of utilization of customary land for the provision of tourist facilities and attractions. Customary land owned by Batuan Traditional Village and Padangtegal Traditional Village in Gianyar Regency, Bali still exists mainly in the form of customary village druwe land. Meanwhile, the Osing Indigenous Community of Kemiren Village in Banyuwangi Regency, East Java is not explicitly recognized as having customary land rights over land or other physical resources. Customary rights are reflected in the ownership of intangible cultural assets/heritage, such as art, rituals, and traditions. The utilization of customary rights for tourism businesses in Batuan Customary Village and Padangtegal Customary Village is managed individually or institutionalized by customary villages based on local regulations. (awig-awig and/or pararem). Whereas in the Osing indigenous community of Kemiren Village there is the utilization of intangible cultural heritage owned by indigenous communities such as art, rituals, and traditions as tourist attractions and attractions.